Understanding Residents’ Perceptions of FEMA Buyout Programs in Small Rural Municipalities: A Case Study of Grifton, North Carolina - Blankenship, Jacob (East Carolina University, 2023)
The small rural town of Grifton, situated between Pitt and Lenoir counties, adjacent to Contentnea Creek, and near the Neuse River in eastern North Carolina (N.C.), has faced several major flood events due to hurricanes. As a result, the community has needed to seek out residential buyouts through the Federal Emergency Management Agency's (FEMA's) Hazard Mitigation Grant Program (HMGP)-a policy tool that aims to mitigate the risks and damages associated with flooding by purchasing properties in flood-prone areas and converting them into open spaces. While deemed beneficial, literature on buyouts indicates that these programs are economically taxing on communities, slow to implement and close out, and introduce possible inequities that impact vulnerable populations and minorities. These issues directly affect homeowners' resiliency and adaptation to flooding, and this research contextualized it in a place-based study-examining eastern N.C. flood events and the risks posed on small rural municipalities. United States (U.S.) Census Bureau data was obtained and compared Grifton and Pitt County, N.C. demographics to note any trends or deviations. Housing Assistance (HA), Hazard Mitigation Assistance (HMA), and Public Assistance (PA) programs were analyzed to show how FEMA responded to federally declared disasters in Grifton. A survey questionnaire was posted in two Grifton Facebook groups to examine residents' familiarity, perceptions, and experience with flood events and buyout programs. 19 individual questionnaire responses were recorded, with respondents noting unfamiliarity with buyout program processes, long disaster recovery times, lack of incentives from FEMA, and uncertainties in buyout finalization. Ideas for future research included conducting GIS analyses, performing cross-sectional and longitudinal studies, and examining land and property values for any notable impacts on Grifton's economy. Recommendations for improvements on buyout programs were proposed, like effective community outreach and education, expediting buyout processes, and increased funding. From this research, scholarly discourse should initiate around FEMA's buyout programs concerned with small rural municipalities like Grifton.
Keywords: major flood events; buyout programs; residential perceptions; Government purchasing of real property--North Carolina--Grifton; United States.--Federal Emergency Management Agency--Appropriations and expenditures; Rural population--North Carolina--Grifton--Attitudes; Flood damage--Economic aspects--North Carolina--Grifton; Flood damage--Social aspects--North Carolina--Grifton; Disaster relief--North Carolina--Grifton--Finance